2021
DOI: 10.3389/fcimb.2021.695299
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Pathway Is Activated by Sulfate Reducing Bacteria

Abstract: Sulfate Reducing Bacteria (SRB), usually rare residents of the gut, are often found in increased numbers (called a SRB bloom) in inflammatory conditions such as Inflammatory Bowel Disease (IBD), pouchitis, and periodontitis. However, the underlying mechanisms of this association remain largely unknown. Notch signaling, a conserved cell-cell communication pathway, is usually involved in tissue development and differentiation. Dysregulated Notch signaling is observed in inflammatory conditions such as IBD. Lipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…This study also suggested that increased abundance of Deltaproteobacteria was causally related to a higher risk of PPH. Deltaproteobacteria is a common pathogenic bacterium, which initiates inflammation by activating the Notch signaling pathway and induces the expression of pro-inflammatory factors including pro-IL-1β and SOCS3 (Jin et al, 2016;Singh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This study also suggested that increased abundance of Deltaproteobacteria was causally related to a higher risk of PPH. Deltaproteobacteria is a common pathogenic bacterium, which initiates inflammation by activating the Notch signaling pathway and induces the expression of pro-inflammatory factors including pro-IL-1β and SOCS3 (Jin et al, 2016;Singh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously showed that administering DSV into the gut of mice caused impaired memory ( Ritz et al., 2016 ) and slowed intestinal transit ( Ritz et al., 2017 ). Recently, we showed that DSV induced Notch signaling pathway which, in turn, upregulated precursors of proinflammatory cascade ( Singh et al., 2021 ). A recent report showed that a proinflammatory SRB Fusobacterium nucleatum induced increased intestinal permeability ( Liu et al., 2020 ) suggesting that SRB may contribute to disease development by disrupting barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…While the pathological role of Desulfovibrio spp. has been studied mainly in the context of their effect on inflammatory pathways ( Weglarz et al., 2003 ; Kushkevych et al., 2019 ; Singh et al., 2021 ), whether these bacteria induce leaky gut is not known even though leaky gut is associated with several diseases related to DSV bloom ( Loubinoux et al., 2002 ). Snail is a transcription factor responsible for increased intestinal permeability ( Forsyth et al., 2011 ; Elamin et al., 2014 ; Liu et al., 2020 ) by negatively regulating TJ proteins such as occludin, claudins, ZO-1 as well as AJ proteins such as E-cadherin ( Cano et al., 2000 ; Martinez-Estrada et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Notch signaling pathway can influence macrophage development indirectly by regulating the expression of macrophage surface marker CD11b [ 36 ]. Relevant studies have pointed out that inhibition of the Notch signal can reduce IL-1β and TNF-α secreted by M1 macrophages, thus reducing the level of inflammatory reaction.…”
Section: Reviewmentioning
confidence: 99%